2009
DOI: 10.2169/internalmedicine.48.2308
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus-associated Acute Gastric Mucosal Lesion in an Immunocompetent Host

Abstract: Involvement of the gastrointestinal tract in cytomegalovirus (CMV) infection is commonly observed in immunocompromised hosts. We encountered an immunocompetent patient with CMV associated-acute gastric mucosal lesion (AGML). The emergence of inclusion bodies characteristic of CMV infection in the speci

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 21 publications
1
23
1
1
Order By: Relevance
“…Apart from nonspecific inflammatory changes, such as increased fragility, hyperemia and/or frank erythema, ulcers or erosions represent the most frequently detected endoscopic changes in UGI infected by HCMV [2,11,16,20,21]. In our study, ulcers were observed in 18/30 patients (60%), being single in 10 cases and multiple in 8, and appeared to be localized mainly in the distal portion of the esophagus and in the antropyloric region.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Apart from nonspecific inflammatory changes, such as increased fragility, hyperemia and/or frank erythema, ulcers or erosions represent the most frequently detected endoscopic changes in UGI infected by HCMV [2,11,16,20,21]. In our study, ulcers were observed in 18/30 patients (60%), being single in 10 cases and multiple in 8, and appeared to be localized mainly in the distal portion of the esophagus and in the antropyloric region.…”
Section: Discussionmentioning
confidence: 52%
“…Although HCMV-induced vasculitis and subsequent ischemic mucosal injury, as a consequence of viral infection in endothelial cells of small vessels, have been postulated to represent the plausible cause of ulceration [12,20], the pathogenesis of hyperplastic changes in the mucosa have not yet been well clarified. Hypothetically, HCMV infection of epithelial or stromal cells in the UGI mucosa might be able to activate different pathways of cell proliferation leading to foveolar hyperplasia, as suggested by in vitro studies [25], in which HCMV gene products were demonstrated to be able to modulate cell-cycle progression and apoptosis inhibition in colon-rectal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…CMV infection in the stomach is frequently reported in normal immunocompetent hosts and is reported to cause gastric ulcers that are difficult to differentiate from Helicobacter pylori - or non-steroidal anti-inflammatory drug (NSAID)-related ulcers and are often accompanied by systemic inflammatory responses such as fever. Even in these cases, the diagnosis of CMV gastric ulcer is not easy, partly because of the absence of characteristic morphological features in gastric ulcers and partly because of the difficulty in the identification of CMV infection in biopsy specimens by routine histomorphological examinations [3, 4, 5]. Therefore, in cases with gastric ulcer and possible CMV infection, additional tests need to be added as appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…Colitis has mainly been reported, but CMV has also been implicated as a cause of symptomatic esophagitis (22), gastritis (23) and ileitis (24) in patients without underlying immunosuppression. While most cases of CMV colitis are secondary to the reactivation of latent infection in immunocompromised patients (7), CMV colitis can occur as a primary infection in immunocompetent patients.…”
Section: Discussionmentioning
confidence: 99%